Blood eosinophil counts, exacerbations, and response to the addition of inhaled fluticasone furoate to vilanterol in patients with chronic obstructive pulmonary disease: a secondary analysis of data from two parallel randomised controlled trials. Issue 6 (June 2015) - Pascoe, Steven; Locantore, Nicholas; Dransfield, Mark T; Barnes, Neil C; Pavord, Ian D
Summary Background The short-term benefits of inhaled corticosteroids for patients with chronic obstructive pulmonary disease (COPD) are greater in patients with evidence of eosinophilic airway inflammation. We investigated whether blood eosinophil count is a useful biomarker of the long-term effect of the inhaled corticosteroid fluticasone furoate on exacerbation frequency. Methods We did a post-hoc analysis of data from two replicate, randomised, double-blind trials of 12 months' duration (Sept 25, 2009 to Oct 21, 2011 and Oct 17, 2011) in which once a day vilanterol 25 μg was compared with 25 μg vilanterol plus 50 μg, 100 μg, or 200 μg fluticasone furoate in patients with moderate-to-severe COPD and a history of one or more exacerbation in the previous year. We compared exacerbation rates according to two baseline eosinophil cell count strata (<2% and ≥2%), and according to four baseline percentage groupings. We also assessed lung function and incidence of pneumonia per strata in treatment groups. Findings We included 3177 patients in the analyses, with 2083 patients (66%) having an eosinophil count of 2% or higher at study entry. Across all doses of inhaled corticosteroids, fluticasone furoate and vilanterol reduced exacerbations by 29% compared with vilanterol alone (mean 0·91 vs 1·28 exacerbations per patient per year; p<0·0001) in patients with eosinophil counts of 2% or higher, and by 10% (0·79 vs 0·89; p=0·2827) in patients with eosinophil counts lower than 2%. Reductions in exacerbations with fluticasone furoate and vilanterol, compared with vilanterol alone, were 24% in patients with baseline eosinophil counts of ≥2–<4%, 32% for those with counts of 4–<6%, and 42% for those with eosinophil counts of ≥6%. In patients treated with vilanterol alone, exacerbation rates increased progressively with increasing eosinophil count percentage category. Improvement in trough forced expiratory volume in 1 s (FEV1) and the increased risk of pneumonia with fluticasone furoate and vilanterol compared with vilanterol alone were not associated with eosinophil count. Interpretation Blood eosinophil count is a promising biomarker of response to inhaled corticosteroids in patients with COPD. Blood eosinophil count could potentially be used to stratify patients for different exacerbation rate reduction strategies. Funding GlaxoSmithKline (study ID 201595).